2016
DOI: 10.1192/bjpo.bp.115.002642
|View full text |Cite
|
Sign up to set email alerts
|

The use of social environment in a psychosocial clubhouse to facilitate recovery-oriented practice

Abstract: BackgroundRecovery-oriented language has been widely adopted in mental health policy; however, little is known about how recovery practices are implemented within individual services, such as psychosocial clubhouses.AimsTo explore how recovery practices are implemented in a psychosocial clubhouse.MethodQualitative case study design informed by self-determination theory was utilised. This included 120 h of participant observation, interviews with 12 clubhouse members and 6 staff members. Field notes and intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Moreover, four papers recommended that vocational rehabilitation interventions have impacted positively on the personalities (eg. sense of competence through participation in work), reduce boredom/loneliness, feeling anchored in reality and create strong internal motivation for change (49,52,55,62). The feelings and expressions of clients help them to develop a sense of self-determination and personal recovery (54,62).…”
Section: Self-e Cacymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, four papers recommended that vocational rehabilitation interventions have impacted positively on the personalities (eg. sense of competence through participation in work), reduce boredom/loneliness, feeling anchored in reality and create strong internal motivation for change (49,52,55,62). The feelings and expressions of clients help them to develop a sense of self-determination and personal recovery (54,62).…”
Section: Self-e Cacymentioning
confidence: 99%
“…Furthermore, some studies suggested that the social environment recovery services, (eg. clubhouse used as a community) have the ability to create an atmosphere of acceptance and inclusion and subsequently support each member's personal recovery journey (54,62). For instance, an adult with severe mental illness in a residential programme (clubhouse) had greater participation in recreational events, informal socialization with peers (44), social relationship, quality of life (30,43) and feeling valued, inclusion and belonging to a group (63).…”
Section: Social Inclusion (Community Integration)mentioning
confidence: 99%
“…Recent Clubhouse literature has begun to reclaim the recovery ideology embodied in the model [27,[30][31][32][33][34][35][36]. Raeburn et al [32], for instance, reviewed samples of key programme documents within an Australian Clubhouse to assess how they reflect recovery ideology.…”
Section: The Ideological Foundations Of the Clubhouse Modelmentioning
confidence: 99%
“…Clubhouses, on the other hand, are non-governmental, non-profit organisations that also provide evening and weekend activities (Norman, 2006). The clubhouse approach to psychosocial rehabilitation originated in the US in the 1940s and has since developed into the established Clubhouse Model (Raeburn, Schmied, Hungerford, & Cleary, 2016). It has been implemented in over 300 sites internationally (McKay, Nugent, Johnsen, & Lidz, 2016) and there are currently 12 clubhouses in Sweden (Sveriges Fontänhus Riksförbund, 2016).…”
Section: Day Centres and Clubhousementioning
confidence: 99%